A New Sensorless Speed Control Scheme for Doubly Fed Reluctance Generators - Ademi, Sul; Jovanovic, Milutin G.; Chaal, Hamza; Wenping Cao (IEEE transactions on energy conversion, 2016)
This paper presents the development and experimental validation of a novel angular velocity observer-based field-oriented control algorithm for a promising low-cost brushless doubly fed reluctance generator (BDFRG) in wind power applications. The BDFRG has been receiving increasing attention because of the use of partially rated power electronics, the high reliability of brushless design, and competitive performance to its popular slip-ring counterpart, the doubly fed induction generator. The controller viability has been demonstrated on a BDFRG laboratory test facility for emulation of variable speed and loading conditions of wind turbines or pump drives.